"Someone to walk with me" : supporting caregivers who look after children with mental health problems in statutory care : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy at Massey University School of Sociology, Social policy and Social Work - Wells, Philippa Mary (Massey University, 2004)
The role of support to caregivers in strengthening care outcomes was explored for a group of children and young people with mental health problems in the care of the Department of Child, Youth and Family Services. Four studies were integrated in a mixed methods design. In the first study a survey of 237 social workers established that informal support and caregiver factors were regarded as more effective than formal support services to caregivers in strengthening care outcomes for this group. Social workers described poor access to mental health services and deficiencies in their support to caregivers looking after children and young people with mental health problems. In the second study a focus group of caregivers viewed effective support as constituting a number of factors, including, informal support from caregiver networks, boundary setting by caregivers, training and support in managing behaviours and participation by children and young people in school or work. The role of religious beliefs, religious networks and respite care, in strengthening care outcomes was emphasised. Caregivers identified poor levels of support from Child, Youth and Family social workers and from mental health services. In the third study, a composite construct for measuring positive care outcomes for children and young people with mental health problems was established by a group of Child, Youth and Family experts, using a Delphi process. In the final study, case history data for a large group (n=1071) of children and young people with mental health problems in care of Child, Youth and Family were explored in a multivariate analysis. This analysis utilised, as independent variables, those factors identified by social workers and caregivers in studies one and two. The composite criterion designed in study three was employed as the dependent variable in this study. Multiple regression procedures provided some evidence for the role of religiously affiliated care and respite care in strengthening care outcomes for this group. The implications of these findings for Child, Youth and Family are discussed.
Keywords: Social services; Caregiver support; Mental health services; Fields of Research::370000 Studies in Human Society::370200 Social Work::370204 Counselling , welfare and community services